Oral health status of the disabled compared with that of the non-disabled in Korea: A propensity score matching analysis - Lee, Jae-Young; Lim, Kyung-Cheol; Kim, So-Yun; Paik, Hye-Ran; Kim, Young-Jae; Jin, Bo-Hyoung (PloS one, 2019)
There are many types of disabilities, and each type has a variety related to socioeconomic factors. Such factors affect to many health problems of the disabled. However, surveys of the oral health status of the disabled in Korea are rare. The purpose of this study was to estimate oral health disparity through comparing oral health status of the disabled to the non-disabled, adjusted for the net effect of the disability on oral health status. A cross-sectional study was conducted among the disabled in urban and suburban areas in Korea from June to September 2016. People with physical, mental, and multiple disabilities took part in this survey. The clinical examinations were carried out by trained dentists. Statistical analysis was performed to quantify the association between oral health and socioeconomic status after restricting the analysis using a propensity score matching method. The disabled had more DMFT, DT, and MT, fewer FT, and fewer teeth than the non-disabled based on entire groups (P<0.01). No difference in the ratio of periodontitis was observed. The subjects with mental disabilities (MD) scored 3.09 (95% CI, 1.07-8.97), and those with multiple disabilities scored 4.37 (95% CI, 1.16-16.37) for edentulous status. The MD had an odds ratio of 1.34 (95% CI, 1.03-1.74), and those with multiple disabilities had an odds ratio of 1.75 (95% CI, 1.11-2.76) for the DMFT index. These results represent poor oral health status of the disabled compared to the non-disabled. Consequentially, we can verify that not only the existence of disability but also the type of disability has a decisive effect on oral health condition. This comparison is necessary to widen our approach to evaluate the actual status condition of the disabled.